P1163Correction of septal flash excursion with his bundle pacing. (18th June 2020) - Pujol-Lopez, M; San Antonio, R; Jimenez Arjona, R; Guasch, E; Doltra, A; Sitges, M; Roca-Luque, I; Trotta, O; Quinto, L; Arbelo, E; Alarcon, F; Garre, P; et al.
Abstract: Funding Acknowledgements: Grant from the Catalan Society of Cardiology Background: His bundle pacing (HBP) directly stimulates the conduction system and could therefore correct asynchrony and evolve as a more physiological pacing approach. Septal flash (SF) is a fast contraction and relaxation of the septum occurring during the isovolumetric contraction period. It is a specific marker of cardiac dyssynchrony. Purpose: Evaluate whether HBP corrects SF in patients with an indication for CRT or RV pacing. Methods: A cohort of 20 consecutive patients undergoing HBP at our center was analyzed. HBP indications were: Group A (n = 3): left bundle branch block (LBBB) and left ventricular (LV) dysfunction (LV ejection fraction [LVEF] < 35%); Group B (n = 14): LV dysfunction (LVEF < 50%) and atrio-ventricular block requiring permanent pacing; Group C (ablate&pace, n = 3): atrio-ventricular node ablation due to rapid atrial fibrillation. Patients in groups B and C had a RV backup lead implanted, in line with current recommendations. The presence of SF was analyzed in 2D-echocardiography at 15 days post-implant. SF excursion was quantified using M-mode in parasternal short and long axis views as the highest amplitude of the early inward motion. Baseline SF excursion was determined during intrinsic rhythm (group A) or RV pacing (groups B and C). For each patient, the pair of measurements (baseline, HBP) in the axis with the highest baseline SF was selected. Results: Mean LVEFs were 21 ± 8%, 32 ± 6%, and 41 ± 18% for groups A, B and C, respectively. HBP shortened QRS duration by 42 ± 15 ms and 45 ± 23 ms in groups A (Baseline QRS - HBP QRS) and B + C (RV pacing QRS - HBP QRS), respectively. At baseline, all patients except 1 had SF (Fig. 1A). The mean SF excursion was 4.3 ± 1.9 mm, with SF excursion being larger in group A than in the RV-paced groups (6.3 ± 1.5 mm vs. 3.9 ± 1.8 mm for groups A and B + C, respectively, p = 0.04). HBP abolished SF in 3 patients (15%) and, on average, decreased SF excursion by 2.3 mm (95% CI 1.3-3.2), irrespective of pacing indication (Fig. 1B). The degree of SF excursion reduction after HBP significantly correlated with QRS shortening (r = 0.53, p = 0.024) (Fig 1C). Conclusions: In conclusion, we show that HBP results in acute correction or decrease of SF, thereby improving LBBB- or RV-induced mechanical dyssynchrony.